The Arctic Incident : Artemis Fowl #2 - Colfer, Eoin (New York : Talk Miramax Books/Hyperion Books For Children, 2002)
When a twelve-year-old evil genius tries to restore his family fortune by capturing a fairy and demanding a ransom in gold, the fairies fight back with magic, technology, and a particularly nasty troll.
BC 06/02, KK 05/15/02, PW 04/15/02
1219
Keywords: Fairies -- Fiction; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; England -- Fiction